Is Change in Hemoglobin Level a Predictive Biomarker of Tyrosine Kinase Efficacy in Metastatic Renal Cell Carcinoma? A Turkish Oncology Group Study. (21st April 2017) - Bilir, Cemil; Yıldız, İbrahim; Bilici, Ahmet; Ucar, Mahmut; Berk, Veli; Yıldız, Yaşar; Yazıcı, Ozan; İmamoğlu, Gökşen İnanç; Karadurmuş, Nuri; Pilancı, Kezban Nur; Arpacı, Erkan; Tanrıverdi, Özgür; et al.
ABSTRACT: Background : There are insufficient predictive markers for renal cell carcinoma (RCC). Methods : A total of 308 metastatic RCC patients were analyzed retrospectively. Results : The increased hemoglobin (Hb) group had significantly higher progression-free survival and overall survival (OS) compared with the decreased Hb group at 11.5 versus 6.35 months ( p < .001) and 21.0 versus 11.36 months ( p < .001) respectively. The 1- and 3-year OS rates were higher in the Hb increased group, i.e., 84% versus 64% and 52% versus 35% respectively. Conclusions : The present study showed that increased Hb levels after tyrosine kinase inhibitor therapy could be a predictive marker of RCC.